Solar radiation over a roof in the presence of temperature-dependent thermal conductivity of a Casson flow for energy saving in buildings. (October 2022) - Abbas, Amir; Noreen, Asma; Ashraf Ali, Masood; Ashraf, Muhammad; Alzahrani, Eman; Marzouki, Riadh; Goodarzi, M.
Abstract: Non-Newtonian Casson fluid has great importance in biomechanics, processing of polymer, and industries. Therfore, in the current study, the solar radiation effects onCasson fluid flow and heat transfer over an exponentially stretching sheet in the presence of the influence of the temperature-dependent thermal conductivity are investigated. The propsoed mechanism is given a mathematical form in terms of partial differential equations. Using appropriate similarity variables for similar solutions, a set of partial differential equations are then reduced into set of ordinary differential equations. The solutions of transformed equations are determined by employing the MATLAB built-in function bvp4c. The solutions of velocity distribution, temperature field, and concentration profile are computed against sundry parameters and portryed in graphs. The skin friction, heat transfer rate, and mass transfer rate versus pertinent parameters are displayed in tables. The numerical outcomes show that as Casson parameter β and radiation parameter N are augmented velocity field rises and reduces with increasing values of Prandtl number Pr and thermal conductivity variation parameter γ . The temperature of fluid is enhaced as N is raised and revese trend is noted for increasing values of β, Pr, and γ . Concentration profile grows well with augmentation in N and γ and reverse behavior is observed for augmenting values of β and Pr . A comparision of present and existing results is given to validate of current solutions.